Histological And Morphological Characterization Of Rat Skin After Cw Co2 Laser Irradiation - Mahmood, Tengku Lina Izzati Raja (2013)
The laser-skin interaction was studied by using the Sprague Dawley rats as experimental samples and continuous wave carbon dioxide laser (CW CO2) as a source of irradiation. Light microscope and field emission scanning electron microscope (FESEM) were used to evaluate the skin surface and underlying structures for both exposed and control samples. Briefly, the rats were divided into two groups with different setting exposures. In the first group, the rat skin was exposed to CW CO2 laser at different power densities (15.63 W/cm2, 17.19 W/cm2, 18.75 W/cm2 and 20.31 W/cm2). Each power density was exposed in four different exposure durations (15 s, 30 s, 45 s and 60 s). The results showed an increase on thermal damage depth and a decrease on epidermal thickness with the increase in both exposure duration and power density. However, the sample exposed at 20.31 W/cm2 showed different features. The damage depth was increased at 15 s and 30 s and then the thermal damage depths were decreased at 45 s and 60 s due to the laser ablation. These observations showed that the ablation effect strongly depended on the exposure duration which then decreased the depth of thermal damage. In the FESEM images, the disruption of corneocytes and the formation of the intervening spaces between corneocytes correlated well with the increase in exposure duration and power density. In fact, dramatic changes were noted in the skin surface, which was treated by the laser at 20.31 W/cm2 with several deep holes that could be seen in the FESEM image. As for the second group, the power density of 20.31 W/cm2 was irradiated at different areas of the skin (side, chest, stomach and leg).